Estudo estatístico do comportamento dos prótons no fim do alcance do feixe de protonterapia - Cerutti, Fabrício Loreni da Silva (2024)
This study focuses on analyzing the output characteristics of proton beams used in proton therapy. When utilizing proton beam energy for image reconstruction, it is essential to consider the statistical behavior of protons to minimize the irradiation dose while simultaneously obtaining reliable data for accurate image reconstruction. Therefore, the aim of this study was to evaluate the sensitivity of the proton (hydrogen) beam output characteristics on a target composed of water molecules, across different beam energies (170 MeV to 180 MeV) and varying thicknesses of the target material, using Monte Carlo simulations (SRIM Software). The proton beam output characteristics evaluated were average energy, number of protons, and total average energy in relation to the thickness of the irradiated object at the end of the range. These parameters are fundamental for optimizing proton therapy, as they allow for a more precise definition of the target volume, minimizing the exposure of healthy tissues to radiation and increasing the effectiveness of the treatment. The simulations revealed that the region where a sudden change in the number of protons occurs is between 170 and 177 MeV. The range of absorber thicknesses corresponding to the end-of-range region is between 20.6 and 22.3 cm. The uncertainty in defining the thickness, which corresponds to variations in the measurement of the target depth, obtained through the analysis of the average output energy, is significantly smaller than the uncertainty related to the number of protons, which indicates the number of protons interacting with the target. As the thickness approaches the end of the proton range, the uncertainty obtained through the final average energy begins to increase rapidly. The uncertainty obtained through the number of protons behaves oppositely and becomes smaller than the uncertainty obtained through the final average energy in the second half of the range region. The uncertainty obtained through the total average energy, unlike that of the final average energy, remains small as the thickness increases and, in the second half of the range region, coincides with the uncertainty obtained through the number of protons. The results suggest that total average energy is the most promising characteristic for proton therapy, as it not only reflects variations in the final average energy but also indicates a pathway toward improving precision in target definition. This could lead to more effective and safer treatments with fewer side effects for patients.